COVID-19 Pandemic: Our Experience in Pakistan - Siddiqui, Atif Hafeez (International Journal of Human and Health Sciences (IJHHS), 2022)
COVID-19 emerged as a horrible nightmare for the humans on earth. This was not only because of the nature of the illness, diversity of symptoms, its bizarre course and unpredictable fate but also due to the broad spectrum of challenges the healthcare system faced across the globe. These challenges include the limited knowledge about the disease, shortage of dedicated COVID-19 facilities, gross deficiencies of Personal Protective Equipment (PPE), diagnostic kits, medicines, equipment for assisted ventilation and several other things necessary for COVID-19 management. Besides sparsely available resources, the myths and denial of COVID-19 had created conspiracies among the masses were even a bigger and a new kind of challenge that probably the medical fraternity has never faced in the recent past. Pakistan Islamic Medical Association (PIMA) realised its responsibility as a leading organisation of doctors, accepted all the challenges, stood tall and firm, putting all its efforts and capabilities to counter the COVID-19 at all fronts. The presentation covers the experiences faced by PIMA and its role during the COVID-19 pandemic in the last two years. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S10